Metabolic and cardiovascular outcomes of bariatric surgery. Issue 4 (August 2020) - Iqbal, Zohaib; Adam, Safwaan; Ho, Jan H.; Syed, Akheel A.; Ammori, Basil J.; Malik, Rayaz A.; Soran, Handrean
Abstract : Purpose of review: Bariatric surgery is an effective therapy for morbid obesity that also improves weight-related metabolic parameters and reduces morbidity and mortality. The purpose of this review is to consolidate our current understanding of metabolic, macrovascular and microvascular benefits of bariatric surgery and to provide an update. Recent findings: Early resolution of insulin resistance and type 2 diabetes mellitus (T2DM) varies by type of bariatric surgery and appears to be mediated by changes in secretion of gut hormones, metabolism of bile acids, expression of glucose transporters and the gut microbiome. Dyslipidaemia, atherosclerosis, microvascular complications of obesity and diabetes, systemic and tissue-level inflammation show evidence of regression and hypertension improves significantly after bariatric surgery. Summary: Bariatric surgery leads to improvements in obesity-related metabolic comorbidities such as dyslipidaemia, HDL functionality, hypertension, T2DM, insulin resistance and inflammation. It slows the atherosclerotic process and reduces cardiovascular and all-cause mortality. Recent data have demonstrated regression of the microvascular complications of obesity and diabetes including the regeneration of small nerve fibres. The magnitude of change in short-term metabolic effects depends on the surgical procedure whilst longer term effects are related to the amount of sustained excess weight loss.